A Mucoadhesive Electrospun Nanofibrous Matrix for Rapid Oramucosal Drug Delivery. (29th October 2013) - Dott, Clare; Tyagi, Charu; Tomar, Lomas K.; Choonara, Yahya E.; Kumar, Pradeep; du Toit, Lisa C.; Pillay, Viness
Abstract : A nanofibrous matrix system (NFMS), consisting of a drug-loaded nanofiber layer, was electrospun directly onto a polymeric backing film, the latter of which was formulated and optimized according to a 3-level, 3-factor Box-Behnken experimental design. The dependent variables, fill volume, hydroxypropylmethylcellulose (HPMC) concentration, and glycerol concentration, were assessed for their effects on measured responses, disintegration time, work of adhesion, force of adhesion, dissolution area under curve (AUC) at 1 minute, and permeation AUC at 3 minutes. Physicochemical and physicomechanical properties of the developed system were studied by rheology, FTIR, toughness determination, mucoadhesion, and nanotensile testing. Data obtained from the physicomechanical characterization confirmed the suitability of NFMS for application in oramucosal drug delivery. The optimized NFMS showed the drug entrapment of 2.3 mg/1.5 cm 2 with disintegration time of 12.8 seconds. Electrospinning of drug-loaded polyvinylalcohol (PVA) fibers resulted in a matrix with an exceedingly high surface-area-to-volume ratio, which enhanced the rate of dissolution for rapid oramucosal drug delivery. To corroborate with the experimental studies, the incorporation of glycerol with HPMC and PVA blend was mechanistically elucidated using computer-assisted modeling of the 3D polymeric architecture of the respective molecular complexes to envisage the likely alignment of the polymer morphologies affecting the performance of the nanofibrous device.